Didymocarpus longicalyx (Gesneriaceae), a new species from southwestern Yunnan, China - Zhang, Cai-Fei; Tian, Jing; Peng, Shuai; Wang, Jun-Jie; Wang, Yan; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2020)
Didymocarpus longicalyx, a new species of Gesneriaceae from southwestern Yunnan Province, China is described and illustrated based on detailed morphological comparisons with all known species of the genus Didymocarpus from both China and neighbouring countries. Morphologically, it is most similar to D. medogensis and D. glandulosus, but can be distinguished by its puberulent peduncles, calyx with ca. 8 mm long segments and claret corollas with three yellow spots and a few yellowish striations on upper lip.